Dispensation of Marriage Age: Istishlah Analysis - Sarkanto; Sukron Mubarok; Muhammed Zaki Tamami; Baedhowi (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
Marriage that occurs at too young an age can pose certain risks, such as domestic violence. Law Number 1 of 1974 on Marriage stipulates that the minimum age for marriage is 19 years for men and 16 years for women. However, in special situations, such as premarital pregnancy, an age dispensation for marriage may be granted to couples who have not reached the minimum age set by law. This paper aims to examine the istishlah (public interest) perspective on the minimum age for marriage according to positive law and the Compilation of Islamic Law. It also explores the perspective of istishlah on the dispensation of marriage age. The research method used in this paper is library research, where the study is conducted by gathering data or scholarly literature related to the topic. In-depth analysis of the research object is carried out through critical examination of relevant sources, focusing on addressing fundamental issues. Considerations of maslahah mursalah (unrestricted public interest), which emphasize benefits and the avoidance of harm, are central. In Islamic law, the minimum marriage age can vary depending on the social and cultural context, as Islam does not explicitly set a minimum age. However, the minimum age in the Compilation of Islamic Law (KHI) is determined based on considerations of public welfare and the prevention of harm. The granting of marriage dispensations prioritizes the avoidance of harm over the pursuit of certain family benefits or welfare.